Plan estratégico para la finca agrícola “Sevilla”, recinto el Vergel, cantón Valencia - Santana Salazar, Víctor Fabián (2017)
The present research work "Strategic plan for the agricultural estate" Seville, "Vergel area, Canton Valencia", aimed to: diagnose the current situation of the farm, establish directional bases and strategic guidelines, which allows defining the actions of The farm, and to make a proposal of the strategic plan that help the growth of the same in order that the owner can carry out a good administration. Thus, for the development of the theoretical framework the topics and sub-themes with respect to this research are detailed, such as: administration, planning, importance of planning, plans, types of planning, principles, strategic planning, SWOT analysis ETC. Being a descriptive research, and applying the inductive / analytical methods for the execution of this project, all this with the support of the primary and secondary sources that allowed us to obtain the data collection, to obtain the results we proceeded to carry out 15 surveys, acquiring necessary information to meet the established objectives, data that were tabulated with the excel application. However the results obtained were not satisfactory, so they demonstrated deficits in which the company does not have a strategic plan being a relevant value of 100%, neither has vision and mission, manual of functions therefore this project developed a proposal for That the farm has excellent management. The conclusions and recommendations that were obtained after having carried out the analysis of the research were formalized. Bibliographic sources support concepts and definitions. Survey form is attached. Key words: Plan - strategic, agricultural.